2011
DOI: 10.3989/scimar.04235.23a
|View full text |Cite
|
Sign up to set email alerts
|

Combining literature review, acoustic mapping and in situ observations: an overview of coralligenous assemblages in Liguria (NW Mediterranean Sea)

Abstract: Summary:A review and update of the existing knowledge on the coralligenous assemblages of Liguria (NW Italy) was conducted as an essential step towards management measures for their conservation according to the EU Marine Strategy Framework Directive. By combining a literature review, acoustic mapping and in situ observations on a geographic information systems platform, we were able to assess the distribution and heterogeneity of coralligenous assemblages and the main pressures affecting them. The reliability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
(14 reference statements)
3
20
0
Order By: Relevance
“…It was characterized by the abundance of large, massive, or erect sponges, including Axinella polypoides , Sarcotragus foetidus , Spongia lamella , Dysidea avara , and Scalarispongia scalaris . Similar epibenthic communities have been described for coralligenous reefs in other Mediterranean regions (Bedulli, Bianchi, Morri, & Zurlini, ; Ben Mustapha et al, ; Cánovas Molina et al, ; Garrabou et al, ), but have not yet been recognized either by EUNIS or by the handbook for the classification of Mediterranean habitats (Pergent, Bellan‐Santini, Bellan, Bitar, & Harmelin, ). We propose, therefore, that a ‘Facies with Axinella polypoides ’ category be included in the next revision of EUNIS.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…It was characterized by the abundance of large, massive, or erect sponges, including Axinella polypoides , Sarcotragus foetidus , Spongia lamella , Dysidea avara , and Scalarispongia scalaris . Similar epibenthic communities have been described for coralligenous reefs in other Mediterranean regions (Bedulli, Bianchi, Morri, & Zurlini, ; Ben Mustapha et al, ; Cánovas Molina et al, ; Garrabou et al, ), but have not yet been recognized either by EUNIS or by the handbook for the classification of Mediterranean habitats (Pergent, Bellan‐Santini, Bellan, Bitar, & Harmelin, ). We propose, therefore, that a ‘Facies with Axinella polypoides ’ category be included in the next revision of EUNIS.…”
Section: Discussionsupporting
confidence: 67%
“…The first concern of the management plan for the Gallinara sea floor should be the reduction of sea‐based human pressures. Early studies suggested that boat anchoring represented the most serious threat to seafloor integrity (Balduzzi et al, ), which has been confirmed by later assessments (Cánovas Molina et al, ; Tunesi et al, ). Anchoring must therefore be banned, and recreational boating regulated (Venturini et al, ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…vertical or near‐vertical walls from a steep littoral rock face) and banks (according to the original substratum: rock or sediment) (Ballesteros, ). Although both forms may be relatively shallow depending on the environmental conditions, rims characterize mostly coastal rocky systems, whereas banks mainly occur on deeper continental shelfs (Cánovas‐Molina et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most important coastal ecosystems of the Mediterranean Sea for distribution, biodiversity, productivity and role in the CO 2 cycle (Bertolino et al 2013, Martin et al 2014, Casas-Guell et al 2015. Coralligenous habitat is considered sensitive to human activities (Piazzi et al 2012, Cánovas Molina et al 2016) and has been included in the protection programme of European legislation (e.g. the Habitats Directive 92/43/EEC; the Marine Strategy Framework Directive 2008/56/EEC) as a habitat of high scientific interest and biodiversity ("special habitat type" sensu MSFD 2008/56/EEC) (EC 2008).…”
Section: Introductionmentioning
confidence: 99%